Value-guided mentoring produces great leaders - Friedman, Daniela B.; Hebert, James R. (Frontiers in Education, 2025)
Leadership rarely follows a clear path. It often emerges from the choices we make, the people we encounter (and who encounter us), relationships we foster, and the values that guide us in our work. In this commentary, we draw on our experiences as researchers, educators, mentors, mentees, and administrators to describe four interconnected themes. We begin with the alignment of our work with personal and professional values, which serves as the anchor for the other three: engaging in mentorship as both mentors and mentees, maintaining resilience through self-care, and leading with confidence in times of uncertainty. These reflections illustrate that leadership is not the outcome of following a detailed “blueprint” or “manual of operations.” Rather than chasing the elusive goal of perfection, leadership should involve showing up grounded in our values and supported by networks of colleagues and communities. Although our experiences are based in public health, we work and thrive in contexts beyond the conventional boundaries of public health, thus the themes we describe have relevance across disciplines. We hope the description of these experiences encourages leaders at different stages to consider values that will strengthen their relationships and prioritize wellbeing, and to act with confidence and courage when facing uncertainty.